Implementation of isoniazid preventive therapy in people living with HIV in Zambia: challenges and lessons - Mary Kagujje; Muhau L. Mubiana; Eugenia Mwamba; Monde Muyoyeta (BMC, 2019)
Abstract Background Uptake of Isoniazid Preventive Therapy (IPT) among People Living with HIV in Zambia has continued to be low despite various evidence for its added benefit in reducing TB incidence and mortality when taken with antiretroviral therapy. In 2017, only 18% of People Living with HIV newly enrolled in care were initiated on IPT in Zambia. Main text Various challenges including policy and management level factors, supply chain factors, health worker perceptions about IPT, monitoring and evaluation factors and limited demand creation activities have constrained the scale up of IPT in Zambia. Lessons that have been learnt while addressing the above challenges are shared and they can be applied by government ministries, project managers, public health specialists to strengthen IPT activities in their settings. Conclusion Zambia has both a high burden of TB and HIV and without preventing new cases of TB from reactivation of latent TB infection, it will be difficult to control TB. All stakeholders involved in prevention of TB among PLHIV need to commit to addressing the challenges limiting scale up of IPT.